Improved performance of phosphonated carbon nanotube-polybenzimidazole composite membranes in proton exchange membrane fuel cells - Kannan, Ramaiyan; Kagalwala, Husain N.; Chaudhari, Harshal D.; Kharul, Ulhas K.; Kurungot, Sreekumar; Pillai, Vijayamohanan K. (Journal of Materials Chemistry, 2011)
Development of thermally stable polymer electrolyte membranes with higher proton conductivity as well as mechanical stability is a key challenge in commercializing PEM fuel cells operating above 100 degrees C. Polybenzimidazole membranes are one of the promising candidates in this category although with limited mechanical stability and moderate proton conductivity. Here the incorporation of functionalized MWCNT is shown to increase both these key parameters of the polybenzimidazole membranes. Further, formation of a domain like structure after the incorporation of phosphonated MWCNTs (P-MWCNTs) in phosphoric acid doped polybenzimidazole membranes is demonstrated. The enhanced performance has been attributed to the formation of proton conducting networks that formed along the sidewalls of P-MWCNTs with a domain size of 17 nm as estimated from the small angle X-ray scattering measurements. Membrane electrode assembly (MEA) impedance measurements further reveal that the activation energy of oxygen reduction reaction (ORR) reduced for the composite membranes with enhanced proton conductivity. In addition, the mechanical strength measurements reveal a significant improvement in the yield strength and ultimate strength. Also, the mechanical strength of the composite membrane has been increased significantly as indicated by the improvement in the ultimate strength from 65 MPa to 100 MPa for the pristine and composite membranes, respectively. The optimum loading of P-MWCNTs is found to be 1% as inferred from the polarization measurements carried out using pure hydrogen and oxygen. Thus, this study provides a unique opportunity to tune the properties of polymer electrolytes to prepare application oriented hybrid membranes using CNTs with tailor-made functional groups.